Penerapan Pendekatan Kontruktivisme dalam Pembelajaran Bahasa Indonesia di SMP Negeri I Remboken - Pelealu, Femmy Tresje (Universitas Sam Ratulangi, 2015)
This study is conducted in order to describe the development model ofconstructivistic teaching in Indonesian language for the sake of maximizing thestudents’ attitude in critical thinking. Operationally this study is done inorder to describe the concept and strategy model and the materials of constructivisticIndonesian language teaching developed by the teachers in SMP Negeri 1 Rembokenfor the sake of maximizing the students’ attitude in critical thinking. TheIndonesian language teachers’ concept on the planning and the conduction ofconstructivistic teaching related to what Indonesian language teaching is, howthe textbook and the materials are used, the purpose of Indonesian languageteaching is, the role of the teacher, the role of the students in the teachingand learning process, the use of teaching methods and media, and the procedureof the conduction of constructivistic Indonesian language teaching and learningprocess in the classroom, was not done by the teachers when they were observed.Their constructivistic teaching attitude is very minimal.